2023
DOI: 10.1111/jerd.13074
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of intraoral scan bodies and their influence on impression accuracy: A systematic review

Aspasia Pachiou,
Evangelia Zervou,
Panagiotis Tsirogiannis
et al.

Abstract: ObjectiveThe aim of this systematic review was to evaluate the influence of the characteristics of intraoral scan bodies (ISBs) on the accuracy of intraoral scanning.Materials and MethodsAn electronic search was conducted through PubMed (MEDLINE), Scopus and Cochrane Library, up to March 2023. The literature search intended to retrieve all relevant clinical and in vitro studies about the effect that the various properties of ISBs may have on the accuracy (trueness and precision) of intraoral scanning. Only pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…The design and material of the scanbody may influence the accuracy of digital impressions, as reported in a recent systematic review, 27 and currently various types of scanbodies have been introduced from all implant manufacturers. The depth of the implant, the fixing torque of the scanbody, the experience of the clinician, the distance between implants and even the multiple use of scanbodies have been reported as factors that potentially affect the accuracy of intraoral scanning of implants 28–35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and material of the scanbody may influence the accuracy of digital impressions, as reported in a recent systematic review, 27 and currently various types of scanbodies have been introduced from all implant manufacturers. The depth of the implant, the fixing torque of the scanbody, the experience of the clinician, the distance between implants and even the multiple use of scanbodies have been reported as factors that potentially affect the accuracy of intraoral scanning of implants 28–35 …”
Section: Discussionmentioning
confidence: 99%
“…Silicone or polyether, open or closed impression tray technique are combining variables for the final result whereas digital impression is not affected by these factors and may explain its superior performance in certain clinical circumstances 24,25 . Accuracy of digital impressions, however, is affected by additional parameters excluding scanbodies which in total play a significant role in the efficacy of the clinical procedure 26–31 . Many studies agree that the impression of the fully edentulous mandible is a clinical challenge for both conventional and digital impression affected in accuracy by many variables 32–35 …”
Section: Introductionmentioning
confidence: 99%
“…The diameter and position of the ISB affect the trueness of implant impressions. After receiving the data from the scan, the software analyzes the data and defines the implants' longitudinal, vertical, and rotational axes [15,16]. Revilla-León et al reported that the optimal ISB design may vary depending on the intraoral scanner (IOS), the materials (PEEK or titanium), the implant angulation, the inter-implant distance, the implant depth, and other factors [17].…”
Section: Introductionmentioning
confidence: 99%